Masnun Tahir's View on the Sociological Construction of the Phenomenon of Nikah Siri in Indonesia - Rosalia Rosalia; Nabila Zanjabila; Indah Khairunisa; Sigit Fiqri Asy’ari; Silmita Zahroh; Keyza Oktaviyani (International Tatho Academics, 2026)
This qualitative study aims to identify the thoughts of Masnun Tahir, a professor of Islamic civil law, on the causes of the phenomenon of unregistered marriages (nikah siri). Primary data was obtained from Masnun Tahir's scientific journal articles. This study uses Soerjono Soekanto's theory of legal effectiveness as a perspective. The results of the study show that, according to Masnun Tahir, the phenomenon of nikah siri is influenced by a low understanding of the law, weak law enforcement, the dominance of cultural norms over state law, and limited access to fair and affordable legal facilities. The findings of this study contribute to the importance of preventive strategies against the complexity of sociological factors causing the rampant cases of nikah siri.